2007
DOI: 10.1080/00288230709510320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus, potassium and lime application on pasture in acid soil in Yunnan Province, China

Abstract: Inadequate provision of winter and early spring forage is a major problem for ruminant production in Yunnan Province, China. Temperate legumes (e.g., white clover) combined with perennial grasses (e.g., perennial ryegrass, cocksfoot) have the potential to fill this feed gap for livestock production when high fertiliser inputs are maintained. In commercial practice, however, these legume/grass pastures perform poorly and lack persistence due to poor fertiliser management. This paper describes a low-input fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Kasa et al [76] found that application of different level of lime and phosphorus significantly increased the yield and yield contributing characters of Haricot bean in Ethiopia. Lime in an acid soil not only replaces hydrogen ions, elevates soil pH [8], and increases NPK availability, but it also promotes plant growth and development in legume crops [77]. In an acidic soil, an experiment was carried out on Sesamum, mungbean, and cowpea with lime applications of 0.5, 1.0, 1.5, and 2.0 tons per hectare, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Kasa et al [76] found that application of different level of lime and phosphorus significantly increased the yield and yield contributing characters of Haricot bean in Ethiopia. Lime in an acid soil not only replaces hydrogen ions, elevates soil pH [8], and increases NPK availability, but it also promotes plant growth and development in legume crops [77]. In an acidic soil, an experiment was carried out on Sesamum, mungbean, and cowpea with lime applications of 0.5, 1.0, 1.5, and 2.0 tons per hectare, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…; Singh and Sale ; Junquan et al . ). Dry weather in 2010 may have muted any fertilization response in the more drought‐sensitive white clover plants.…”
Section: Resultsmentioning
confidence: 97%
“…Unlike red clover, white clover yield was not affected by fertilization in either year. This was surprising as other studies have found a positive effect of fertilization on white clover (Williams et al 1985;Singh and Sale 1998;Junquan et al 2007). Dry weather in 2010 may have muted any fertilization response in the more drought-sensitive white clover plants.…”
Section: Clover Yield and Treatment Effectsmentioning
confidence: 87%
“…It has been reported that new cocksfoot lines are characterized by high biomass productivity (Tarakanovas, Chomiak, 2008;Tilvikienė et al, 2012). The sparse experiments with liming reveal that when growing cocksfoot under severe acid soil conditions in pure sward as well as in mixture with other crops, its productivity is increasing when the lime is applied (Junquan et al, 2007;Poozesh et al, 2010). The effects of different nitrogen rates on cocksfoot biomass and energy productivity are presented by Lithuanian and foreign authors (Mills et al, 2009;Tilvikienė et al, 2012).…”
Section: The Impact Of Lime and Nitrogen Fertilization On Cocksfoot Amentioning
confidence: 99%
“…The impact of lime and nitrogen fertilization on cocksfoot and reed canary grass productivity in Albeluvisol and energy evaluation of their cultivation technology more tolerant of relative high levels of exchangeable aluminium (Al) than many other grass species, the application of 1500 kg ha -1 yr -1 of burnt lime in moderately and strongly acidic soils caused the increase of cocksfoot DM productivity by 2084 kg ha -1 , on average per three years (Junquan et al, 2007).…”
mentioning
confidence: 99%